PENERAPAN QUALITY ASSURANCE PADA PIRANTI LUNAK DENGAN MENGGUNAKAN METODE GRAPH SCENARIO - Lestantri, Indah Dwi (LPPM Politeknik Astra, 2011)
This paper discusses implementation quality assurance based on the methodology of software testing. This method includes scenario testing, graph, test case, path and strategic. The method use in this paper is graph scenario method.